The Analysis of Writing Assessment Types in Textbook English for Nusantara Grade 7 - Yenny Teriana; Ira Maisarah (Universitas Nusantara PGRI Kediri, 2026)
Writing assessment is essential for improving student' writing skill, but thorough studies of how it is implemented in widely used national textbooks are limited. This study aims to identify the types of writing assessment tasks presented in the English for Nusantara Grade 7 textbook and to examine how these tasks align with established writing assessment frameworks. Utilizing qualitative content analysis, all writing activities throughout five chapters were assessed and classified according to Brown's (2004) taxonomy of imitative, intensive, responsive, and extensive, as well as performance-based assessment standards. The findings show a planned evolution of writing assessments. The first chapters are primarily made up of imitative and demanding exercises (for example, matching, filling tables, and listing terminology). These serve as a scaffold for responsive writing tasks (such as concise description or organizational paragraphs) that demand connected discourse. Extensive writing tasks (whole, cohesive paragraphs) are less common, but they do occur in the following sections and enrichment activities. Pre-writing exercises provide valuable support but do not directly test writing abilities. Overall, the textbook aligns moderately with known paradigms, while possibilities for comprehensive writing are inadequate. These results provide insights for enhancing writing assignments in EFL textbooks and point to the need for more study comparing writing assessments throughout materials and investigating the experiences of learners using each assessment type.